2015
DOI: 10.1083/jcb.201407039
|View full text |Cite
|
Sign up to set email alerts
|

A flipped ion pair at the dynein–microtubule interface is critical for dynein motility and ATPase activation

Abstract: Salt bridges at the dynein–microtubule interface couple microtubule binding to ATPase activation and thereby control the directional movement of dynein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 55 publications
10
65
0
Order By: Relevance
“…Experiments by Gibbons et al [31] first suggested that the “α-registry” is associated with a strong binding state of the MTBD and a four residue shifted “β+-registry” is associated with a weak binding state. Several subsequent experiments have provided additional support for this hypothesis [29, 3235]. The sliding of one of the helices of the stalk between the α- and β-registries is thought to provide a mechanism for communicating between the AAA ring and the MTBD.…”
Section: The Dynein Motor Domain and Its Conformational Changesmentioning
confidence: 98%
See 1 more Smart Citation
“…Experiments by Gibbons et al [31] first suggested that the “α-registry” is associated with a strong binding state of the MTBD and a four residue shifted “β+-registry” is associated with a weak binding state. Several subsequent experiments have provided additional support for this hypothesis [29, 3235]. The sliding of one of the helices of the stalk between the α- and β-registries is thought to provide a mechanism for communicating between the AAA ring and the MTBD.…”
Section: The Dynein Motor Domain and Its Conformational Changesmentioning
confidence: 98%
“…Similar to this model, dynein has been shown to undergo one-dimensional diffusion along the microtubule surface in its weakly bound (ATP) state. This result suggests that the MTBD can hold on to the microtubule weakly and that thermal energy can displace the MTBD from one tubulin subunit to the next along the microtubule [35, 53, 54]. Furthermore, optical trap studies have uncovered a directional asymmetry in the binding of dynein to the microtubules.…”
Section: How Dynein Steps Towards the Microtubule Minus Endmentioning
confidence: 99%
“…The assumption that isoforms or post‐translational states can be averaged or overlooked appears to be untrue. Recent work has shown that sequence and modification state can change the dynamics, and the binding of associated proteins and enzymes . Recombinant tubulin from yeast can achieve high purity and has been systematically studied with various mutants .…”
Section: Gtpase Filaments: Microtubules and Tubulin Structure And Funmentioning
confidence: 99%
“…To investigate whether there are specific residues in tubulin that are shared in the interaction with kinesin, PRC1, and dynein, we performed sequence and structural alignments for these proteins, using tubulin as the common element to superimpose the MT-MAP models (Materials and Methods). Although as yet there is no atomic-resolution information on the binding of the dynein MTBD to MTs, hybrid models of this interaction have been generated by integrating diverse sources of data, including crystal structures (41-47), medium-resolution EM maps (43,47), and biochemical data (48,49). Superposition of the MT-kinesin atomic model with our MT-PRC1-SC atomic model identified kinesin R278 and PRC1 R381 as functionally similar in their interaction with tubulin (potentially with β-tubulin D420 and β-tubulin E427) (Fig.…”
Section: Prc1's Disordered C-terminal Domain Forms Electrostatic Intementioning
confidence: 99%
“…Previous atomic models of motor domains bound to MTs derived from cryo-EM reconstructions (43,(45)(46)(47) and crystallography (41) were superimposed on our final atomic model using the H11′ helix on α-tubulin to align the binding pockets locally. The following structures were inspected to identify tubulin residues that potentially share binding activity for PRC1, kinesin, or dynein: 2P4N (42), 4HNA (41), 4CK5 (44), 4UXO (45), 3J8Y (46), 3J6P (47), 3J1U, and 3J1T (43).…”
Section: Simulationsmentioning
confidence: 99%